Factors Influencing the Growth of South Africa’s Agricultural Exports toWorld Markets - Potelwa, Xolisiwe Yolanda; Lubinga, Moses Herbert; Ntshangase, Thandeka (European Scientific Journal, ESJ, 2016)
The paper assesses the factors influencing South Africa’s agricultural export growth to its cardinal destinations between 2001 and 2014. A gravity model was used to present investigation of trade flows that has been validated as a suitable tool in determining export growth. The findings indicate that an improvement in South Africa’s and importer’s GDP causes an increase in agricultural exports. Distance and political stability have been shown to have no influence on the growth of agricultural exports to its trading partners. The importer’s population and the export capacity showed a positive relationship on the growth of South Africa’s agricultural exports to its trading partners. Trading agreements, which include AGOA and the TDCA with the EU, show a positive impact on increase in export performance. Therefore, the results suggest that South Africa should focus on countries with a growing population and GDP to improve agricultural export growth and market diversification.